Lymphokine production by human milk lymphocytes. - Keller, M A (1981)
To assess the functional capability of human milk lymphocytes, we studied phytohemagglutinin-induced lymphokine production by breast milk and, for comparison, peripheral blood lymphocyte cultures. Two lymphokines, lymphocyte-derived chemotactic factor (LDCF) and immune interferon, were assayed in supernatants of milk and blood lymphocyte cultures obtained from women 2 to 6 days postpartum. Eleven parallel milk and blood samples were studied for LDCF production. In nine experiments, both milk and blood lymphocytes produced LDCF. In the two other experiments, milk cells did not produce LDCF. In 10 milk cultures studied, all produced interferon activity. Acid and heat lability characteristics were typical of immune interferon. These results further characterize milk lymphocytes as immunologically competent and possibly important effector cells in neonatal immunity.